Ultra-wide spectral range (0.4–8 μm) transparent conductive ZnO bulk single crystals: a leading runner for mid-infrared optoelectronics. (August 2020) - Cheng, L.; Zhu, S.; Zheng, W.; Huang, F.
Abstract: Transparent conductive oxides have been widely applied to solar cells, liquid crystal displays, and other optoelectronic devices because of their excellent transparent conductive properties in the visible-near-infrared (Vis-NIR) region. At present, the transparent conductive oxide films (TCOFs) such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and aluminum-doped zinc oxide (AZO) are widely noticed and used. However, a high carrier concentration (≥10 20  cm −3 ) of these TCOFs leads to a result that their transparency will be affected by the plasmons effect, and thus their transparent range will generally end around 2–3 μm. As such, they are more applicable in the Vis-NIR region but unable to meet the requirements of mid-infrared (MIR) optoelectronic devices. Faced with this situation, herein, we reported the native ZnO bulk single crystals with low background carrier concentration (10 15 –10 16  cm −3 ) and high carrier mobility (μ > 300 cm 2  V −1  s −1 ). These single crystals boast excellent transparent conductive properties (IR cutoff edge: 6–8 μm, R sheet : 3.7–28.5 Ω/sq) with an advantage that they can be massively produced by a hydrothermal method at a low cost. Based on these merits, the native ZnO bulk single crystals bring a new possibility of breaking the bottleneck of MIR transparent conductivity. Graphical abstract: Image 1 Highlights: The native ZnO bulk single crystals grown by the hydrothermal method possess low background carrier concentration (10 15 –10 16  cm −3 ) and high mobility (μ＞300 cm 2  V −1  s −1 ). The native ZnO bulk single crystals perform excellent transparent conductive properties: IR cutoff edge: 6–8 μm and R sheet : 3.7–28.5 Ω/sq. The decrease of the transmission of the ZnO single crystals with low carrier concentration is related to the free carrier absorption.